Perancangan Interior Woman Health and Beauty di Surabaya - Sherly Setiawan; Sriti Mayang Sari; filipus priyo suprobo (Intra, 2016)
Beauty and fitness center is a place for relaxation and health aimed specifically for women. The hectic lifestyle adapted by women nowadays tends to make them more vulnerable to fatigue and stress. Therefore, the interior design for Woman Health and Beauty in Surabaya is an interior design project for a beauty and fitness center designed to fulfill the need of a facility that will provide complete beauty treatment and fitness training for women in a place with utmost privacy. The designed facilities include the lobby, salon area, nail spa area, spa area, fitness area, yoga area, locker area, toilet dan cafe.